Comprehensive SSR study of 14 Zingiberaceae species based on microsatellite capture sequencing (MiCAPs) - Shi, Miao; Tanaka, Keisuke; Rivera, Marlon P.; Thein, Min San; Ngure, Godfrey M.; Watanabe, Kazuo N. (Frontiers in Plant Science, 2025)
IntroductionThe Zingiberaceae family encompasses numerous species renowned for their significant pharmacological properties and culinary importance. Despite this value, many species remain under-utilized due to the absence of basic molecular information, which hinders effective conservation and sustainable utilization. Simple Sequence Repeat (SSR) markers are particularly suitable for genetic studies in such species, as they are highly polymorphic and do not necessitate a reference genome. Microsatellite capture sequencing (MiCAPs) presents a cost-effective solution by enriching libraries for SSR-containing fragments prior to sequencing, substantially reducing data requirements and costs for marker discovery.MethodsMiCAPs was applied to 160 accessions, including 148 samples from 14 Zingiberaceae species and 12 samples from an outgroup (Musaceae family). SSR marker candidates were developed and evaluated via electronic-PCR (ePCR) for seven target species. Phylogenetic relationships were reconstructed using consensus sequences from MiCAPs data, and genetic similarity patterns were assessed using Polymorphic SSR Retrieval (PSR) analysis across Curcuma and Zingiber species.ResultsA total of 21.78 million raw reads were generated, from which 612 SSR marker candidates were developed. A genus-level phylogenetic tree successfully reconstructed the relationships among the 14 Zingiberaceae species. Comparative genetic diversity analysis revealed that Zingiber exhibits a relatively more conserved genetic background compared to Curcuma.DiscussionThis integrated workflow combining MiCAPs, ePCR, and PSR demonstrates a practical approach for marker development and diversity assessment in polyploid species lacking reference genomes. Despite the genetic complexities inherent in Zingiberaceae, especially potential polyploidy, our approach proved highly effective in establishing a robust phylogenetic framework and enabling comprehensive genetic diversity assessment. The novel set of 612 SSR marker candidates represents a significant resource that will facilitate future genetic studies focused on the diversity, evolutionary relationships, conservation, and sustainable utilization of valuable Zingiberaceae species